A new species of Comorocoris from Northern Madagascar (Hemiptera: Heteroptera: Aradidae) - Baňař, Petr; Heiss, Ernst (Zootaxa, 2018)
A new species Comorocoris estherineae sp. nov. (Hemiptera: Heteroptera: Aradidae: Carventinae) from Montagne d’Ambre National Park in Northern Madagascar is described and illustrated. The newly described species is compared and keyed with all three species of Comorocoris Heiss, 1985 known so far.